HUBUNGAN KECERDASAN NATURALISTIK DAN MINAT BELAJAR DENGAN HASIL BELAJAR BIOLOGI SISWA SMA DI KOTA LUWUK - NURLIA NURLIA; SULASMI ANGGO (JURNAL PENDIDIKAN GLASSER, 2020)
The success of any learning objective is measured from the students’ learning outcomes, which could be influenced by internal and external factors. Internal factors capable of affecting students’ learning outcomes include naturalistic intelligence and learning interest. Hence, the purpose of this study was to describe the relationship between naturalistic intelligence and learning interest, with biology learning outcomes of students in Luwuk City. This was an ex post facto study with a research population of eleventh grade students of Mathematics and Natural Sciences High School in Luwuk City in the 2019/2020 academic year. A proportional random sampling method was used to select 235 out of the 566 students of the grade, as the research subjects. The data collection techniques employed include online questionnaires and documentation, while the analysis techniques used were descriptive and inferential statistics. Based on the results, there was a very low relationship between naturalistic intelligence and biology learning outcomes, there was a low relationship between learning interest with biology learning outcomes, as well as between naturalistic intelligence and learning interest with biology learning outcomes of high school students in Luwuk City.